Risk of Rice Cultivation under Current and Future Environment and Market (Bangladesh Rice Journal, 2021)
Risk is an inevitable feature of agriculture globally, and it might increase over time in the future. The study assesses the risk of rice cultivation in the three seasons under current and future conditions. The software programme @Risk version 7.6 was used to simulate the risk-return trade of rice cultivation in the three seasons in Bangladesh. The likelihood of having negative net income for the Aus (90%) and Boro (80%) rice was very high under the current market and environmental conditions. Besides, the chance of obtaining negative net income was notable for T. Aman (33%). Both the yield and price variation significantly contributed to the fluctuation of returns of rice production. However, with the current seasonal variation in yield, the probability of having negative net income for paddy rice was very low under the farmers’ expected price (Aman: 22.5 BDT kg-1, Boro: 25 BDT kg-1 and Aus: 24 BDT kg-1). The result indicates that only access to the fair price of the rough rice can ensure the economic sustainability of the rice production. Likewise, chances of having a negative net income of paddy rice in 2030 will be zero under the extrapolated yield (Aman: 5.3 kg ha-1, Boro: 6.3 kg ha-1 and Aus: 4.8 kg ha-1) and price (Aman: 31.75 BDT kg-1, Boro: 30.75 BDT kg-1 and Aus: 30 BDT kg-1). The findings indicate that rice cultivation in the three seasons will be economically sustainable, subject to achieving the expected genetic gain and ensuring access to the projected price. Thus, policy supports are needed to ensure farmers' access to a fair price, improve management practice, and strengthen research to enhance genetic gain for sustainable rice farming under future conditions.Bangladesh Rice J. 25 (1) : 101-110, 2021